Dichotomy of Friend” and “Foe” in Structure of Eastern Notes of F. Salten, F. Werfel, E. Canetti - N. E. Seibel; E. M. Shastina (Научный диалог)
The travel notes of three Austrian writers of Jewish origin: “New people in the old land” by F. Salten, “Egyptian diary” by F. Werfel and “Voices of Marrakesh” by E. Canetti are considered. Based on the comparison of texts, typological similarities are distinguished at several levels: firstly, the meaning of travel as a return to the origins in the biographies of writers; secondly, the structural similarity of the motives, composition and chronotope of the notes; thirdly, the repetitive narrative structure of the texts. The fundamental differences revealed in the course of typological analysis are shown, which are associated with the reflection of political events by modern authors, each of them connects the geocultural image of space with its own interpretation of history. It is noted that myth and language are the connecting link of the times for all three, the messianism of the poet is emphasized. The article focuses on the selfdetermination of the narrator in relation to the described world. Overcoming the prejudice of European Orientalism, the authors come to an interested-mentoring (Salten), detached-objective (Werfel) or indifferent position of a flâneur (Canetti). It is concluded that the movement from the enthusiastic utopianism of Salten to the disappointment of Canetti is accompanied by a change in the cyclical concept of history by the idea of eternalism.